Operation triple X - Dhar, Maloy Krishna (New Delhi, 2007)
Set in the background of Indo-pak relationship which historic events witnessed change of leadership in both the countries and two wars reshaped the geography of what is now known as Pakistan, before they carved it from the original Indian continent.
Keywords: English Fiction